PRAKTIK DISKRIMINASI PADA PT.GARUDA INDONESIA (PERSERO), TBK TERKAIT PEMILIHAN MITRA PENJUALAN TIKET UMRAH BERDASARKAN PUTUSAN NOMOR 06/KPPU-L/2020 - Alfifah Wanda Wardanti (2022)
At the beginning of the case, the Business Competition Supervisory Commission (KPPU) decided that PT. Garuda Indonesia (Persero) Tbk. Commit violations related to discrimination and make efforts to close access to distribution channels for direct sales of Umrah tickets to and from Jeddah and Medina through the Wholesaler Program. There is PT. Garuda issued a policy related to selling Middle East Asia (MEA) tickets that required Umrah Travel Organizers (PPIU) to purchase through the five designated Wholesalers. In this case, barriers to entry impacted most of the other Umrah Travel Organizers (PPIU). This policy contradicts Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. This study uses a normative juridical research method using a statutory approach, namely Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition and a case approach, namely Decision Number 06/KPPU-L/ 2020 regarding Alleged Discriminatory Practices of PT Garuda Indonesia (Persero). Based on the results of this study, the Commission Council stated that PT. Garuda Indonesia (Persero), Tbk. proven to have violated Article 19 letter (d) of Law Number 5 of 1999 and sentenced to execution in the form of an administrative penalty of Rp. 1,000,000,000 (one billion rupiah). In this case, not only that, there was a negative impact on related parties, namely, consumers, other umrah travel agencies and agents, and PT. Garuda Indonesia (Persero) Tbk. Itself.